Computing with Excel and VBA a problem solving approach - Krishan, S. I.; Safari eBooks (Sudbury, Mass. : Jones and Bartlett Publishers, 2009)
"Ideal for use in non-majors, introductory-level CS or CIS courses, Computing with Excel and VBA provides students with a clear emphasis on problem solving using the popular tools Excel and VBA. Numerous examples are presented throughout the text to illustrate key concepts, and several additional examples and exercises are provided as learning tools at the end of each chapter. All examples were developed to relate to practical situations that students will likely encounter in their work or studies. By using Excel to demonstrate how computers can be used to solve problems, students will gain a solid skill set in this popular resource. The coverage of VBA provides exposition to programming with simple examples to show how Excel applications can be customized. Computing with Excel and VBA provides students with a concise and complete understanding of computer systems and problem solving techniques that will pave the way for future study!"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Microsoft Excel (Computer file); Microsoft Visual Basic for applications; Business -- Computer programs; Electronic spreadsheets; Problem solving -- Data processing; Electronic books